Status and development prospect of fuel pellet industry in Malaysia - J., M. Nuramin; Saadun, N.; Harun, Z. (Forestry Department Peninsular Malaysia, 2020)
Fuel pellet has become one of the largest traded solid biomass commodities in the global market. The booming fuel pellet market especially in Europe, America and other Asian countries like South Korea and Japan are influenced by various factors including public policies on renewable energy to mitigate climate change, market characteristics, economic factors, and fuel pellet properties. In response to the newly emerging fuel pellet market worldwide, Malaysia has set the aim to position itself as the largest exporters of fuel pellets, especially in Asia. This review looks into the current fuel pellet market situation to describe the role that Malaysia plays in the global market and highlights the opportunities and challenges present for a viable fuel pellet industry in Malaysia based on a review of related kinds of literature. Results showed that Malaysia is still far behind the national target and global rival especially from neighboring countries such as Vietnam and Indonesia in terms of export performance. Nevertheless, the potential for developing the fuel pellet industry is particularly evident in Malaysia given the abundance of biomass resources, supportive government policies and incentives, and strong global demand for fuel pellets. Some of the challenges that need to be addressed for developing a viable fuel pellet industry include attracting foreign investment, increasing market competitiveness, improving efficiency in terms of logistics and supply chain, complying with technical and sustainability fuel pellet standards, and publishing the statistic of fuel pellet trade, price, and knowledge to the public.